Aspek Hukum Penolakan Protokol Kesehatan di Era Pandemi COVID-19 - Mahesa Paranadipa Maikel (Masyarakat Hukum Kesehatan Indonesia, 2021)
Informed consent can be a form of communication between doctors and patients or the patient's family. Apart from Informed consent, there are also other patient statements, namely